THE CATEGORY OF EVALUATION AND ITS REPRESENTATION IN THE SEMANTICS OF METAPHOR - Харкавців, Ірина (SWorldJournal, 2022)
The article is aimed to research the category of evaluation and define the its categorical status. Metaphors with a rational and emotional evaluative components have been analyzed as well as the role of evaluation in the semantics of metaphors have been